2013 15th European Conference on Power Electronics and Applications (EPE) 2013
DOI: 10.1109/epe.2013.6634665
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of 1.2 kV investigation of SiC MOSFETs for aeronautics applications

Abstract: International audienceThis paper evaluates robustness and performances of two types of 1.2 kV SiC MOSFETs in order to investigate these power devices for medium power aeronautics applications. The first part focuses on switching performances with effects of gate resistance and load current level. The second part focuses on robustness results showing the weakness of the gate under short-circuit test

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The thermally activated carrier generation is described by Shockley-Read-Hall (SRH) theory, and the corresponding leakage current is given by (16) [27]…”
Section: Leakage Current Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermally activated carrier generation is described by Shockley-Read-Hall (SRH) theory, and the corresponding leakage current is given by (16) [27]…”
Section: Leakage Current Modelmentioning
confidence: 99%
“…In [13], the short circuit capability of 1200 V / 100 mΩ SiC MOSFETs with active areas of 3.5 mm × 3.5 mm are studied and analyzed at 400 V DC bus voltage, 10 V / 15 V positive gate bias, and 25 o C case temperature. It is shown that the short circuit withstand time (SCWT) is around 80 μs at 10 V gate voltage and 50 μs at 15 V. Similar investigation of 1200 V commercially available devices is reported in [14], with a DC bus voltage of 400 V, gate voltage of +18 / 0 V, and case temperatures of 90 o C and 150 o C. A major concern of these testing results is that the short circuit test conditions may not represent the real application scenarios of 1200 V SiC MOSFETs that usually has a positive gate voltage as high as 20 V and DC bus voltage greater than 600 V. A more practical evaluation of short circuit capability can be found in [15] and [16] with 600 V DC bus voltage, 20 V / -5 V gate voltage, and 25 o C case temperature. However, the temperature dependent short circuit characteristics and associated failure mechanisms have not been investigated.…”
Section: Introductionmentioning
confidence: 98%
“…In [4], SiC MOSFEts have shown high junction operation temperature capabilities (i.e., beyond 250 • C ) for long-term reliability, nevertheless, the short circuit capability has proven to be equivalent to its silicon counterparts. Additionally, the Short Circuit Safe Operation Area (SCSOA) of the latest discrete 1.2 kV SiC MOSFET devices have been lately investigated, evidencing a large variation between different manufacturers (i.e, typically Cree, Rohm, GE) [5]- [7] and testing conditions (i.e., DC link voltage, case temperature, and gate voltage) [8], [9], [13]. Other studies have focused on the development of an electro-thermal model for predicting the SCSOA, including failure time and simulated junction temperature at different testing conditions, such as those in [10], [14].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, there has been a special emphasis on SiC Metal-Oxide-Semiconductor Field-Effect Transistors (MOSFETs) [1]. The benefits of using SiC MOSFETs compared with Silicon (Si) Isolated-Gate-Bipolar-Transistors (IGBTs) has been identified in many applications such as aeronautics [4], automotive [5], wind turbine [6] and, soft switching converters [7], [8]. The SiC MOSFET is currently under mass production, mainly due to the fact that it is comparably uncomplicated to replace Si IGBTs with SiC MOSFETs.…”
Section: Introductionmentioning
confidence: 99%